Pengaruh Penghambatan Enzim Siklooksigenase-2 dan Aktivitas Antiinflamasi dari Ekstrak Daun Ketumbar (Coriandrum sativum L.) - Ifora, Ifora; Sintia, Bella; Srangenge, Yoneta (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Inflammation is a normal protective response to tissue damage that mediated by Cyclooxygenase-2 (COX-2) enzyme. The enhancement incidence and impact of inflammatory diseases have encouraged the search for new pharmacological strategies to overcome the problem. Ketumbar (Coriandrumsativum L.) has been traditionally used as an anti-inflammatory and antioxidant, thus giving chance for anti-inflammatory studies. This study aims to determine the ethanol extract of Ketumbar (Coriandrumsativum L.) leaves anti-inflammatory activity and inhibitory effect on COX-2 enzyme. This study uses male wistar rats with 180–220 g body weights. The rats is divided into six groups by the dose of 125 mg/kg BW, 250 mg/kg BW, and 500 mg/kg BW; positive control (Carrageenan 1%); negative control (Na. CMC 0,5%); and comparative group (Celecoxib 9 mg/kg BW). Determining the anti-inflammatory activity, the oedema formation is measured using a plethysmometer and the inhibition activity is determined by ELISA methods. The results showed that the ethanol extract of Ketumbar leaves by the dose of 125 mg/kg BW, 250 mg/kg BW, and 500 mg/kg BW was significantly inhibitted COX-2 valued 65,61%, 76,83%, and 62,93%. The anti-inflammatory activity was shown by inhibiting oedema valued of 62.26%, 70.59%, and 54.90% respectively. These findings suggested that the ethanol extract of Ketumbar leaves had anti-inflammatory activity, that was possibly mediated through inhibition of COX-2 enzymes